Digital Teaching for Sustainable Development in Early Childhood Education: A Case Study of University C - Qingyue, Pang (INTI International University, 2025)
Driven by the global wave of digitalization, digital transformation has become one of the key pathways to achieving modernization and equity in education. Although numerous studies on digitalization have been conducted, research on digitalization in the field of preschool education remains scarce. Therefore, this study selects University C as a case to analyze the current status of digitalized preschool education operation and proposes corresponding solutions. Using interviews and questionnaires, the study focuses on teachers from the Preschool Education Department of University C to investigate the development of digitalization in preschool education at the university. The research finds a series of problems, such as teachers’ lack of ability to utilize digital teaching resources, imperfect digital supporting facilities, and monotonous teaching methods. Based on these issues, the following recommendations are proposed: first, enhance teachers’ ability to use digital teaching resources; second, increase financial investment; and third, enrich the content and methods of course design. This provides a reference for promoting the digital development of preschool education in the future.